Early Presbyopia A Psychosomatic Disorder - Arshad Shaikh, M. S. Fahmi, Uzma Fasih, M. Rais, Atiya Rahman (Pakistan Journal of Ophthalmology, 2014)
Purpose: To evaluate the frequency of factors associated with early presbyopia among patients presenting in the outpatient department. Material and Methods: The study was carried out in outpatient department of Spencer Eye Hospital Unit 2 Karachi Medical & Dental College from January 2012 to August 2013. Patients were selected from the OPD through non probability consecutive sampling technique and included 246 patients. Sample size was calculated by WHO formula given by L Lamesho and SK Lawanga. Patients below 40 years were included in the study who presented with complaint of decreased near vision. Majority of them were those who complained of inability to see the font of cell phone. Patients having ocular pathologies that could affect the clarity of medias like corneal opacities, cataract, uveitis, vitritis and retinal detachment were excluded from the study. A detailed history of the patients was taken regarding any disorder, tobacco use, any refractive error, glaucoma and occupation, Base line investigations as blood complete picture, urine detailed reporting, random and fasting blood suger were also done as and when required. Patients were examined thoroughly in the OPD and were refracted and appropriate glasses prescribed. Data analysis was done on SPSS version 14. Results: There were 40% male patients and 60% female patients with mean age of patients 35.6 ± 4.01 years. Tobacco chewers who presented with early presbyopia were 88 (35.7%). Fifty Two (21.1%) patients had gastritis and 18 (7.31%) had hypertention. Sixteen (6.50%) patients were diabetic. Ten (4.06%) had both diabetes and hypertention. Computer operators with early presbyopia were 5 (6.09%). Presentation of patients with refractive errors was 14 (5.69%). Less prevalent factors associated with early presbyopia were smoking 7 (2.85%) patients, glaucoma 5 (2.03%), anaemia 5 (2.03%), thyroid disease 4 (1.6%), history of use of hair dyes 4 (1.6%), osteoarthritis 2 (0.81%) and allergic disorders 2 (0.81%). Patients who presented with no specific cause were 4 (1.62%). Conclusion: Early presbyopia is not uncommon in a society with associated psychosomatic disorders due to stressful social, environmental and financial conditions. People are anxious and they have habit of nicotine and tobacco abuse. Associated gastritis, hypertension and headache are further indicators of early presbyopia being a psychosomatic disorder. Key words: Presbyopia, Psychosomatic disorder, Refractive errors.